Da'wah Method Through Interreligious Dialogue On the Tiktok Account @Yusuf.Pi.3 - Fauji Ilyas; M. Nofrizal Amir; Riva Yahdi Putri (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
The development of social media, especially TikTok, has created a new space for da'wah activities that are not only monologic, but also dialogic, involving adherents of various religions. This study aims to analyze the application of the da'wah method through interfaith dialogue using TikTok. This study highlights how the Al-Bayanuni concept approach related to the da'wah method is implemented through interfaith dialogue using TikTok. The method used in this study is a descriptive qualitative approach with interviews, observation, and documentation as data collection techniques. The results show that the da'wah method through interfaith dialogue on the TikTok account @yusuf.pi.3 refers to the da'wah method according to Al-Bayanuni, which consists of the Sentimental da'wah method (Heart to Heart) demonstrated by the use of polite, firm, and clear language; the Rational da'wah method (Head to Head) demonstrated by opening dialogue sessions and question-and-answer sessions related to Islamic teachings; and the Sensory method (High Value to High Value) demonstrated by the use of visualizations to clarify the meaning of Quranic verses.